PENERAPAN STRATEGI PEMBELAJARAN MIND MAPPING DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS IV PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI DI SDN 004 SEBERANG TALUK HILIR KECAMATAN KUANTAN TENGAH - Yori Okviana; Sopiatun Nahwiyah; Zulhaini Zulhaini (JOM FTK UNIKS (Jurnal Online Mahasiswa FTK UNIKS), 2020)
In the learning process each student is less motivated, the solution to overcome this is by implementing learning strategies that are interesting and fun for students, one of which is to apply the Mind Mapping learning strategy, namely by creating study groups and then conveying the results of their respective discussions - motivation so that students learning PAI and Character increases. The purpose of the authors conducted research was to determine student learning motivation that affects student learning outcomes in the field of Islamic education and character of fourth grade elementary school students by implementing Mind Mapping learning strategies at SDN 004 Seberang Taluk Hilir. As subjects in this study were 1 Islamic Education teacher and all students SDN 004 Seberang Taluk Hilir which measures 12 people consisting of 6 men and 6 women and as an object is the application of Mind Mapping learning strategies in increasing the learning motivation of fourth grade students of SD Negeri 004 Seberang Taluk Hilir, Central Kuantan District. Based on the results of learning data by means of observation, interviews and documentation. This proves that the increase in student learning motivation from cycle to cycle II with the proportion of 16.66% (pre-cycle), 53.33% (cycle I), 66, 66% (cycle II), so the learning motivation of the fourth grade students of SDN 004 Seberang Taluk Hilir increases.